1971
DOI: 10.1139/f71-283
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Persistence of DDT in a Lotic Ecosystem

Abstract: DDT persisted in streams of several small watersheds in Maine for at least 10 years following light applications to the forest. Residues declined sharply within 2 or 3 years after application, but after 10 years were still well above concentrations detected in untreated streams. This was true of all components studied: muds, plants, invertebrates, fish, and fish-eating birds. The prolonged persistence led to cumulative residue levels in streams sprayed more than once. Concentration of residues through the food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1973
1973
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The slow conversion of DDT to DDE in water has also been shown (29). DDT has been found to decrease slowly but only over a matter of years in fish (30), crayfish (31), and aquatic ecosystems (32). The toxicity of DDT to fish is inversely proportional to their size (33,34).…”
Section: Resultsmentioning
confidence: 99%
“…The slow conversion of DDT to DDE in water has also been shown (29). DDT has been found to decrease slowly but only over a matter of years in fish (30), crayfish (31), and aquatic ecosystems (32). The toxicity of DDT to fish is inversely proportional to their size (33,34).…”
Section: Resultsmentioning
confidence: 99%
“…1973). Some areas have received up to three applications of DDT between 1954(Dimond et al 1971. In quests for DDT substitutes, malathion was tested in 1964 (Dimond 1967), Zectran in 1967 and (Coughlin 1971), fenitrothion (Accothion) in 1970 (Nash et al 1971), and Bacillus thuringiensis Berliner in 1963 (Klein and Lewis 1966), in 1972 (Dimond 1972), and in 1973 (Dimond 1974).…”
Section: Introductionmentioning
confidence: 99%
“…and reported that insecticides virtually disappeared from water within 24 hours. Several other workers have reported much larger residues in mud than in the water above it (Simmons, 1945;Dimond et al, 1971;Miles and Harris, 1971;Rowe et al, 1971). There seems little doubt that just as some soils can adsorb more pesticides than others, so some types of mud bottom can bind more pesticide.…”
Section: Mud Bottommentioning
confidence: 92%
“…Nevertheless, residues persist in the bottom mud for a long time. For instance, Dimond et al (1971) showed that DDT persisted in small streams for 10 years after a single application.…”
Section: From Sprayingmentioning
confidence: 99%